Food Sovereignty and Popular Feminism in Brazil - Motta, Renatta (2023)
The Marcha das Margaridas is a coalition of women and feminism movements, agrarian movements, trade unions, and international organizations that emerged in 2000. Women’s organizations that are part of a rural trade federation lead the process. While its initial agenda included gendered class-based demands for the recognition of women’s work in food production, access to land titles and labour rights, the Marcha das Margaridas progressively incorporated other topics, such as agroecology and food sovereignty. The article addresses three questions: How did food sovereignty enter their agenda? What is the meaning of food sovereignty for them? How can food sovereignty be understood from a (popular) feminist perspective? Based on an analysis of the political documents, we identified five main themes in the discourse of the Marcha das Margaridas on food sovereignty: 1) food as a right and a common; 2) state support for women’s food production; 3) the value of uncommodified food work; 4) environmental recovery through agroecology; 5) violence-free food, produced through respectful social relations.